Efficacy and Toxicity of Whole Pelvic Radiotherapy Versus Prostate-Only Radiotherapy in Localized Prostate Cancer: A Systematic Review and Meta-Analysis - Wang, Shilin; Tang, Wen; Luo, Huanli; Jin, Fu; Wang, Ying (Frontiers in Oncology, 2022)
Background There is little level 1 evidence regarding the relative efficacy and toxicity of whole pelvic radiotherapy (WPRT) compared with prostate-only radiotherapy (PORT) for localized prostate cancer. Methods We used Cochrane, PubMed, Embase, Medline databases, and ClinicalTrials.gov to systematically search for all relevant clinical studies. The data on efficacy and toxicity were extracted for quality assessment and meta-analysis to quantify the effect of WPRT on biochemical failure-free survival (BFFS), progression-free survival (PFS), distant metastasis-free survival (DMFS), overall survival (OS), gastrointestinal (GI) toxicity, and genitourinary (GU) toxicity compared with PORT. The review is registered on PROSPERO, number: CRD42021254752. Results The results revealed that compared with PORT, WPRT significantly improved 5-year BFFS and PFS, and it was irrelevant to whether the patients had undergone radical prostatectomy (RP). In addition, for the patients who did not receive RP, the 5-year DMFS of WPRT was better than that of PORT. However, WPRT significantly increased not only the grade 2 or worse (G2+) acute GI toxicity of non-RP studies and RP studies, but also the G2+ late GI toxicity of non-RP studies. Subgroup analysis of non-RP studies found that, when the pelvic radiation dose was >49 Gy (equivalent-doses-in-2-Gy-fractions, EQD-2), WPRT was more beneficial to PFS than PORT, but significantly increased the risk of G2+ acute and late GU toxicity. Conclusions Meta-analysis demonstrates that WPRT can significantly improve BFFS and PFS for localized prostate cancer than PORT, but the increased risk of G2+ acute and late GI toxicity must be considered. Systematic Review Registration PROSPERO CRD42021254752.